Sistem Pakar Diagnosa Penyakit Pencernaan dan Solusi Penanganan dengan Metode Forward Chaining Berbasis Web - Saiful, Muhammad; uddin, 'Alim (Infotek : Jurnal Informatika dan Teknologi, 2020)
Indigestion is a disorder caused by abnormalities in the digestive system that come from food or a person’s physical condition. Indigestion in children is usually a functional disorder caused by immaturity or immaturity of the digestive system, where most of the body’s immune system formation comes from the the digestive tract. The design of this expert system uses forward chaining as a method in which the user  must provide data or facts before the infrenceengine works or processes. So that the inference engine traces the knowledge base according to the data or facts provided to produce a final conclusion. This expert system is more focused  on one object which is called indigestion experienced by children, so that is expected to produce an expert system that is effective and accurate in handling indigestion in children early. And can provide information to users whether or not further treatment requires treatment by a doctor.DOI : 10.29408/jit.v3i1.1816